SOME CONSIDERATIONS REGARDING THE STRENGTH CALCULUS OF A LATHE TOOL - Catălin ROŞU (Fiabilitate şi Durabilitate)
In this paper a strength calculus of a lathe tool is made. The main purpose of this study is to determineequivalent stress relations that can be useful for an engineer in the design situation. The simplifying assumptionsand the equivalent stress relations are presented from an original point of view.